A study to evaluate the problems faced by recovery officers to regularize default loan accounts in national housing finance and investments limited. - Samantha, Nafisa Tasnim (Brac University, 2021)
This internship report is submitted in partial fulfillment of the requirements for the degree of Masters of Business Administration, 2020.